L’âme, prison du corps ? À propos d’un détail du Theophilus in carcere - Eric Méchoulan (Les Dossiers du GRIHL)
Following Michel Foucault’s suggestion about the “soul, prison of the body”, which inverses the traditional conception of the body as prison of the soul, I will scrutinize a detail of Viau’s Theophilus in carcere (the astonishing reference to Danae) that permits him paradoxically to capture/ captivate his judges. This detail is exemplary of the way surveillance and enprisonment produces a “soul”, which transforms one’s body into an archive of one’s self.